(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The foundation of an agriculture economy that guarantees sustenance and healthful security for a populace of over a billion, crude material for an extending modern base, surpluses for exports, and a reasonable and impartial reward framework for the cultivating network requires responsibility driven contract cultivating which unmistakably is a suitable elective cultivating model. Previous literature reveals that several Indian and multinational companies have already begun contract farming initiatives in India and have been broadly successful. It is found that their success is dependent on a profitable market, the physical and social environment, and government support. However, effort is needed to reduce negative impacts which arise from contract farming via the active involvement of institutions governing the contract farming business. The overall future of contract farming in India is quite promising due to increasing trend for organised retailing amongst the burgeoning middle class population and the food safety requirements of the export market in developed countries.